Multi-locus genome-wide association study for phosphorus use efficiency in a tropical maize germplasm - Zeffa, Douglas Mariani; Júnior, Luiz Perini; de Assis, Rafael; Delfini, Jéssica; Marcos, Antoni Wallace; Koltun, Alessandra; Baba, Viviane Yumi; Constantino, Leonel Vinícius; Uhdre, Renan Santos; Nogueira, Alison Fernando; Moda-Cirino, Vania; Scapim, Carlos Alberto; et al. (Frontiers in Plant Science, 2024)
Phosphorus (P) is an essential macronutrient for maize (Zea mays L.) growth and development. Therefore, generating cultivars with upgraded P use efficiency (PUE) represents one of the main strategies to reduce the global agriculture dependence on phosphate fertilizers. In this work, genome-wide association studies (GWAS) were performed to detect quantitative trait nucleotide (QTN) and potential PUE-related candidate genes and associated traits in greenhouse and field trials under contrasting P conditions. The PUE and other agronomy traits of 132 maize inbred lines were assessed in low and normal P supply through the greenhouse and field experiments and Multilocus GWAS was used to map the associated QTNs. Wide genetic variability was observed among the maize inbred lines under low and normal P supply. In addition, we confirm the complex and quantitative nature of PUE. A total of 306 QTNs were associated with the 24 traits evaluated using different multi-locus GWAS methods. A total of 186 potential candidate genes were identified, mainly involved with transcription regulator, transporter, and transference activity. Further studies are still needed to elucidate the functions and relevance of these genes regarding PUE. Nevertheless, pyramiding the favorable alleles pinpointed in the present study can be considered an efficient strategy for molecular improvement to increase maize PUE.